What determines the long-run growth in Sub-Saharan Africa? Exploring the role of energy, trade openness and financial development in six countries - (:unkn) unknown (My University, 2015)
This paper investigates the effect of energy effciency, international trade and ﬁnancial development on long-run income per capita growth of six Sub-Sahara African (SSA) countries, namely Botswana, Cameroon, Kenya, Senegal, South Africa and Togo. The Autoregressive Distributed Lag (ARDL) bound approach to cointegration is applied with (possible) structural breaks to examine both the short-term and long-term effects. Furthermore, generalized forecast error variance decomposition is applied to decompose the forecast variance of GDP per capita attributable to the selected independent variables. The long-term results show that trade openness and ﬁnancial development affect positively and signiﬁcantly income per capita in South Africa and Kenya, respectively. A compelling evidence of energy effciency involvement in growth is found in Togo. The short-term estimations highlight the signiﬁcant role of investment and energy in output process in virtually all the countries and the role of trade openness in South Africa and Togo. The ﬁndings also provide major policy implications for sustainable economic growth in SSA countries.
Keywords: African Research